Respon Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) dengan Aplikasi Pupuk Kandang Ayam yang Diperkaya Trichoderma spp. - Sibahuddin, Sibahuddin; Susanti, Hilda; Dewi, Indya (Agroekotek View, 2023)
This study aims to determine the effect of the interaction between the doses of chicken manure and Trichoderma spp. on the growth and yield of Shallot due to different doses of fertilizing chicken manure and Trichoderma spp., as well as obtaining the number of doses that gave the best plant growth and yield. This research was conducted at the Greenhouse of the Faculty of Agriculture, ULM Banjarbaru, which started from June to August 2019. This study used a factorial Completely Randomized Design of two factors, namely (1). Chicken manure: 10:20:30:40 t/ha, and (2). Trichoderma spp.: 14:24:34 g/polybag. Each treatment combination was repeated 3 times. The variables observed included plant height, number of leaves, number of tillers, number of tubers, tuber wet weight and tuber dry weight.The results obtained after observations were made, namely, there was no interaction between the doses of chicken manure and Trichoderma spp. on the overall growth and yield of shallot plants. The single factor doses of chicken manure had an effect on the variable plant height of 1 WAP, while Trichoderma spp. effect on the dry weight of shallot plants. The treatment of 10 t/ha of chicken manure resulted in onion plant height with the best yield of 52.00 cm, while the treatment of 34 g/polybag Trichoderma spp. yielded the best dry weight of shallots at 10.21 g/plant.